2020
DOI: 10.1080/13691457.2020.1818059
|View full text |Cite
|
Sign up to set email alerts
|

Marginalised groups protest against social welfare and public health: conceptualising the challenge for social workers

Abstract: As neoliberalisation and other global disruptions change the understanding of human rights and social justice for social workers, how are protests organised by marginalised groups against social welfare and public health regimes understood and participated, or even resisted, by social workers? Although there is a vast literature on protest and community organising in the social work tradition, there is less exploration of marginalised groups organising against the systems in which social workers are employed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Even in an example when the dissensus happened to disrupt social workers’ own arrangement, it has been regarded as barbarian noise and violently suppressed. Only after criticism were the protesters given a space for speech within the consensus of social work from the benevolent social workers (Aaslund and Chear, 2020). As social work researchers, we risk misrepresenting acts of Darstellung as acts of Vertretung when reporting on apparently progressive projects with short-term positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even in an example when the dissensus happened to disrupt social workers’ own arrangement, it has been regarded as barbarian noise and violently suppressed. Only after criticism were the protesters given a space for speech within the consensus of social work from the benevolent social workers (Aaslund and Chear, 2020). As social work researchers, we risk misrepresenting acts of Darstellung as acts of Vertretung when reporting on apparently progressive projects with short-term positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Standing by and fighting together with the disadvantaged who face social injustice, social workers can be perceived as activists who pursue social justice (Shokane & Masoga, 2019). As Aaslund and Chear (2020) highlight that when social workers commit themselves in collective actions or social movements, their professional identity and ethical perspectives are aligned for the betterment of the marginalized groups. Children, women, the elderly, people with disabilities, indigenous, and sexual minorities make up the majority of social work's target audience.…”
Section: Social Workers Are Protestersmentioning
confidence: 99%
“…As Gray et al (2002) found, a variety of roles can be played by social workers in social movements, including communicator, advocate, voter, lobbyist, persuader, collaborator, campaigner, individualist, witness, and activist. Still, the roles social workers play in addressing the psychological problems caused by social movements remain to be elucidated (Aaslund & Chear, 2020). In addition, although there is vast literature explaining the causes of social movements from a psychosocial perspective (van Stekelenburg & Klandermans, 2013), it seems worthwhile to pay more attention to the psychosocial consequences caused by social movements.…”
Section: Introductionmentioning
confidence: 99%